2020
DOI: 10.3390/su12124846
|View full text |Cite
|
Sign up to set email alerts
|

Migration Intentions of Romanian Engineering Students

Abstract: This paper aims to diagnose Romanian engineering students in relation to their migration intentions, motivations, and destinations, and to predict the magnitude of migration in the polled population. It presents the results of a quantitative study based on a questionnaire survey consistent in terms of number and structure of variables and responses. The online questionnaire was self-administered by 1782 students from the five major technical Romanian universities, which are the main providers of the highly ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Although there have been numerous studies conducted on various topics related to the polytechnic university environment in Timis , oara, such as migration, student values, the development of the concept of sustainability in the University's strategic plan, the use of educational resources, Artificial Intelligence [AI], etc. [18,[38][39][40], none have addressed the issue of online education, either from the perspective of the students or from that of the teachers. Nevertheless, as there are no studies to be found on the perspective of students' online behaviour regarding choosing not to turn on their webcams, as well as on the usage of webcams and their effect on students' behaviour and impact, the present research aims, on the one hand, to identify the motives that the students at the Politehnica University of Timis , oara have regarding the use of webcams in online classes, whatever their behaviour and, on the other hand, to find solutions to improve the online educational process.…”
Section: Contextual Behaviour Of Webcam Users In the Education Online Environmentmentioning
confidence: 99%
“…Although there have been numerous studies conducted on various topics related to the polytechnic university environment in Timis , oara, such as migration, student values, the development of the concept of sustainability in the University's strategic plan, the use of educational resources, Artificial Intelligence [AI], etc. [18,[38][39][40], none have addressed the issue of online education, either from the perspective of the students or from that of the teachers. Nevertheless, as there are no studies to be found on the perspective of students' online behaviour regarding choosing not to turn on their webcams, as well as on the usage of webcams and their effect on students' behaviour and impact, the present research aims, on the one hand, to identify the motives that the students at the Politehnica University of Timis , oara have regarding the use of webcams in online classes, whatever their behaviour and, on the other hand, to find solutions to improve the online educational process.…”
Section: Contextual Behaviour Of Webcam Users In the Education Online Environmentmentioning
confidence: 99%
“…The three-stage approach allows for highlighting the embedded motivators of students for action and interaction, offering possible predictions concerning the assemblage they are likely to form after graduation, mainly in a social sense. While the number of engineering graduates in Romania is higher than the European Union average [29], a heavily significant proportion of students ponder migration in search of higher payment and better career opportunities than the ones offered in their home country [35]. The participants in the study, conducted from November 2019 to February 2020, were students enrolled in the five major technical universities of Romania, namely Politehnica University of Bucharest (UPB), the Technical University of Civil Engineering of Bucharest (UTCB), the Technical University of Cluj-Napoca (UTCN), Gheorghe Asachi Technical University of Ias , i (TUIASI), and Politehnica University Timis , oara (UPT), higher institutions that educate over 80,000 students at the levels of Bachelor, Master, Doctorate [36].…”
Section: Methodsmentioning
confidence: 89%
“…The research team involved in the present study draws inspiration from the existing body of literature and looks into Romanian engineering education, focusing on the values and beliefs of students, i.e., future engineers, portrayed by various reports not only as professionals-to-be, but also as people-on-the-go, animated by nomadic predispositions, and relying more on individualistic goals than on an interest in the public good [28,29]. Offering an alternative view to the mainstream opinion, namely that the stability of a highly skilled workforce in a region is a prerequisite for sustainable development, Deleuze and Guattari associate nomadism with free spaces for thinking as "nomads think without limits or boundaries and, in the process, generate creative and imaginative frames of thinking" [25] (p. 9).…”
Section: The Rhizomatic Proposalmentioning
confidence: 99%
“…About Territory and Environment, and in terms of migration, coverage of the brain drain in demography and geography, though later, it is thematically natural [92,139]. Among all these themes, Economics and Politics, as in other social phenomena, is preponderant due to thematic economization, consistent with the recognition of the economy as the main engine of mobility of advanced human capital [140]. Such WoS category alone represents participation in practically a third of the registered articles.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, and as a precautionary note, scholars need to be aware that beyond the change of direction in the national effects, they need to extend their analysis to other countries when countries consider themselves destination countries. For example, scholars must focus their analysis beyond countries with a high level of development, which constitutes a new challenge in this line of research toward the study of the effects of the brain drain in the peripheral areas of knowledge production, contributing to a better understanding of the phenomenon in those geographic areas and design new public policies, in the economic dimension of sustainability [17], to strengthen innovation and local industry [32,47,140,[155][156][157]. Likewise, public policies should be approached from a logic of adaptation to the global mobility of advanced intellectual human capital (brain circulation) and not only from a drain perspective [12,158] and with a greater emphasis on the intellectual human capital attraction policies and not principally focused on brains retention or forced return [45], avoiding the research groups break [159] and promoting geographically distributed research [160][161][162][163].…”
Section: Discussionmentioning
confidence: 99%